2003
DOI: 10.1152/advan.00002.2003
|View full text |Cite
|
Sign up to set email alerts
|

Guided Development of Independent Inquiry in an Anatomy/Physiology Laboratory

Abstract: Student-originated projects are increasingly utilized in the biology laboratory as a means of engaging students and revitalizing the laboratory experience by allowing them one to two weeks to collect data on a manipulated variable of their choice by use of an introduced technique. Such experiments fail as good models of investigative learning when they place more emphasis on novel ideas than on hypothesis testing, experimental design, statistical rigor, or use of the primary literature. In addition, students g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 6 publications
4
37
0
Order By: Relevance
“…The result lends weight to an argument for research skill development to occur in consecutive courses of the undergraduate years (Boyer Commission, 1998) to enable skills to reinforce, rather than to atrophy. The findings are in agreement with discipline-specific studies in regards to explicit development leading to improved research skills (Chaplin, 2003;Hoskins et al, 2007;Luckie et al, 2004).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The result lends weight to an argument for research skill development to occur in consecutive courses of the undergraduate years (Boyer Commission, 1998) to enable skills to reinforce, rather than to atrophy. The findings are in agreement with discipline-specific studies in regards to explicit development leading to improved research skills (Chaplin, 2003;Hoskins et al, 2007;Luckie et al, 2004).…”
Section: Discussionsupporting
confidence: 87%
“…One realistic way of bringing teaching and research together in learning environments is for academics to explicitly develop student research skills in regular semester-length courses (Chaplin, 2003;Hoskins, Stevens, & Nehm, 2007;Luckie, Maleszewski, Loznak, & Krha, 2004), immersing students in the discipline, not only for its content, but also for its knowledge-making practices (Chanock, 2004). Determining the methods and outcomes of explicitly developing student research skills is a contemporary international agenda, with the goal 'to move more curricula in the direction of developing students as participants in research and inquiry' (Jenkins & Healy, 2009, p. 6, emphasis added).…”
Section: Introductionmentioning
confidence: 99%
“…Hypothesis testing and predictions have been widely used as learning tools to promote active learning (3,6,10,35,39,40). Several studies have demonstrated the effectiveness of the use of hypothesis testing and/or predictions as learning tools (5,8,26,30,31,42).…”
mentioning
confidence: 99%
“…Students see the data being collected in real time and can interact and manipulate their recordings immediately. According to multiple groups, incorporating these systems as part of a transition to active-learning-based laboratory curricula improves learning outcomes and student perceptions of learning (Casotti, Rieser-Danner, & Knabb, 2008;Chaplin, 2003;Zimmermann & Eckert, 2010). The real-time nature of the system is beneficial, as delays in producing the graphical output from generated data can inhibit learning of the underlying concept (Brasell, 1987).…”
Section: Active Learning In the Anatomy And Physiology Laboratorymentioning
confidence: 99%